2003
DOI: 10.1111/j.1349-7006.2003.tb01385.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent suppression of hyperlipidemia and intestinal polyp formation in Min mice by pioglitazone, a PPARγ ligand

Abstract: In our previous study, a peroxisome proliferator-activated receptor γ γ γ γ (PPARγ γ γ γ) agonist, pioglitazone, suppressed both hyperlipidemia and intestinal polyp formation in Apc 1309 mice at doses of 100 and 200 ppm in the diet. In contrast, it has been reported that doses of 1500 or 2000 ppm of another PPARγ γ γ γ agonist, troglitazone, enhanced colon polyp development in Min mice. In the present study, we therefore investigated the effects of a wide range of pioglitazone doses on both hyperlipidemia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 25 publications
7
83
0
Order By: Relevance
“…Pioglitazone also could effectively suppress intestinal polyp development in Min mice (Niho et al, 2003). Thus, pioglitazone might be a good candidate for a chemopreventive agent against obesity-associated colorectal cancer.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Pioglitazone also could effectively suppress intestinal polyp development in Min mice (Niho et al, 2003). Thus, pioglitazone might be a good candidate for a chemopreventive agent against obesity-associated colorectal cancer.…”
Section: Discussionmentioning
confidence: 95%
“…At the same time of first intraperitoneal injections, pioglitazone was administrated at concentrations of 400 or 800 ppm in basal diet. The dosage of pioglitazone was determined by our previous experiment (Niho et al, 2003). Food and water were available ad libitum.…”
Section: Experimental Protocol For Kk-a Y Mice Treated With Azoxymethmentioning
confidence: 99%
See 2 more Smart Citations
“…Serum levels of triglycerides and cholesterol have been shown to be positively associated with colon carcinogenesis (38,39). Niho et al found that serum levels of triglycerides in Min mice are dramatically increased compared to the wild-type and the increase contributes to the growth of small intestinal polyps (40). They also demonstrated that a peroxisome proliferator-activated receptors (PPAR)Á ligand suppresses both serum triglyceride level and intestinal polyp formation in Min mice (40).…”
Section: Discussionmentioning
confidence: 99%